Test report no. PLBO/10: reducing flank wear by controlled elastic deflection of the tool holder - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
Cutting tests were carried out on tips of RD 92, cutting EN9 at 600 fpm, 0.010 in/rev. feed and 0.10 in. depth of cut, with a standard tool holder and with a tool holder which had been modified in such a way as to reduce the contact between the clearance face of the tool tip and the workpiece when the tool holder deflected elastically. The results of the tests showed that up to 0.030 in. flank wear the modified tool holder gave tool lives which were about 20% better than those obtained using the standard tool holder.